Evauasi Kesesuaian Retensi Hara untuk Tanaman Bawang Merah (Allium ascalonicum) di Kecamatan Baktiraja Kabupaten Humbang Hasundutan Sumatera Utara - Dicky Alamsyah Pulungan; Supriadi Supriadi; Bintang Sitorus (Jurnal Agroekoteknologi, 2015)
The aim of this research is to evaluate the suitability of nutrient retention for Shallot (Allium ascalonicum) in Baktiraja Sub-district of Humbang Hasundutan District, North Sumatera Province. The method of this search is survey method with Purposive Random Sampling Method with 30 samples and 3 meters, which is pH, CEC, and C-Organic. The result of this research show that land quality nutrient retentiont at Baktiraja Sub-District of Humbang Hasundutan District for shallot (Allium ascalonicum) is moderately suitable (S2). The characteristics for pH and C-Organic are highly suitable (S1), and at the same time is moderately suitable (S2) for CEC.Keywords: Shallot, pH, CEC, C-Organic